Putting transition at the centre of whole-of-curriculum transformation. - O'Donnell, Marcus; Wallace, Margaret; Melano, Anne; Lawson, Romy; Leinonen, Eeva (Student Success v.6 n.2 p.73-79 https://doi.org/10.5204/ssj.v6i2.295, 2015)
This article describes the development of a model for institution-wide curriculum transformation at the University of Wollongong (UOW). Transition - a curriculum-integrated approach that enables a smooth, supported shift into and through higher education and a successful transition from the university to the world of work and lifelong learning - is one of three key principles at the heart of the UOW Curriculum Model. The article focuses on transition as a whole-of-curriculum design principle and the way this principle informs the other elements of the UOW Curriculum Model. It aims to extend the concept of 'transition pedagogy' developed by Kift and colleagues and to show how it has been used to inform the university's larger project of curriculum renewal. [Author abstract]